1990
DOI: 10.1002/eji.1830200411
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD8+ thymocytes are susceptible to DNA fragmentation induced by phorbol ester, calcium ionophore and anti‐CD3 antibody

Abstract: Stimulation of murine thymocytes with phorbol ester or calcium ionophore for 18-24 h resulted in 70%-80% fragmentation of DNA into 180-200-bp multiples, followed by cell death. Experiments with fractionated subpopulations by panning or flow cytometry revealed that DNA fragmentation was selectively observed in CD4+CD8+ cells and in a portion of CD4-CD8+ cells. To investigate whether DNA cleavage is also inducible via antigen-specific receptors, thymocytes were incubated in wells precoated with anti-CD3 antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 27 publications
2
39
0
Order By: Relevance
“…Preferential apoptosis of the CD4 ϩ CD8 ϩ thymocyte subset by anti-CD3 Ab has been well-documented in vivo as well as in vitro (31)(32)(33)(34). Previous studies indicate that thymic macrophages are the principal stromal cells responsible for phagocytosis of dying thymocytes and that the number of TUNEL-positive thymocytes declines to the original basal level after apoptotic cells are phagocytosed by macrophages in the thymus following administration of anti-CD3 Ab or hydrocortisone (28,35).…”
Section: Slpi Expression In Thymuses After Administration Of Anti-cd3mentioning
confidence: 99%
“…Preferential apoptosis of the CD4 ϩ CD8 ϩ thymocyte subset by anti-CD3 Ab has been well-documented in vivo as well as in vitro (31)(32)(33)(34). Previous studies indicate that thymic macrophages are the principal stromal cells responsible for phagocytosis of dying thymocytes and that the number of TUNEL-positive thymocytes declines to the original basal level after apoptotic cells are phagocytosed by macrophages in the thymus following administration of anti-CD3 Ab or hydrocortisone (28,35).…”
Section: Slpi Expression In Thymuses After Administration Of Anti-cd3mentioning
confidence: 99%
“…29 In brief, thymocytes were lysed in the buffer containing 10 mM Tris-HCl (pH 8.0), 0.5% N-lauroylsarcosine and 0.1 M EDTA, and treated with 100 mg/ml proteinase K and 50 mg/ml RNase A. The DNA was extracted by phenol/chloroform and precipitated in isopropyl alcohol containing 0.5 M NaCl.…”
Section: Cell Preparations and Cell Culturementioning
confidence: 99%
“…Stimuli that are normally mitogenic for T cells can induce cell death in transformed T-cell hybridomas (1,20,21,23,26,33) and in untransformed T cells (19,30,34). This process, activation-driven cell death, can be triggered by the presentation of appropriate antigen as well as by treatment with lectins and antibodies specific for the T-cell receptor complex (TCR) or other activation structures on the T-cell surface, such as Thy-1 and Ly-6 (20,21,33).…”
mentioning
confidence: 99%
“…Negative selection in vivo has been shown to act preferentially on immature CD4+ CD8+ T cells (7,13). In thymic organ culture (6,27) and in vitro (19,30), these double-positive cells also appear to be more sensitive to TCR-mediated activation-driven cell death than are more mature T cells. Conversely, while mature T cells are susceptible to activation-driven cell death triggered via phosphatidylinositol-linked membrane proteins Thy-i and Ly-6 (34), it has been reported that stimulation via Thy-i does not induce T-cell death in thymic organ cultures (27).…”
mentioning
confidence: 99%